Lecture comparative dans la poésie de Prévert et d’al-Sayyab Towards a Comparative Reading in Prévert and Al-Sayyab’s Poetry (Journal of the College of Languages (JCL), 2014)
Comparative literature is one of the important research topics in finding new relations and results that other types of studies do not allow.The present research is a comparative study between two contemporary poets : Al-Sayyab and Prévert. The reason for accomplishing this research is Al-Sayyab’s reading for the western literature. Moreover, the study sheds a light on translational criticism.It tackles the lives of the two writers and their points of similarities and differences. Prévert and Al-Sayyab’s are two modern poets. The first employed his daily routines to express reality, specially the events of the two world wars. The second’s pain, on the other hand, was the starting point to express others’ suffering. As far as their themes are concerned, rain has a distinct role in their writing that showed bitterness of life as well as hope for a brighter future.This study finds a new relation that connects the two writers. It is translation. Although Al-Sayyab is famous of his modern poetry, he is unknown to readers as a translator. He translated poems for many writers. Jacques Prévert was one of them. He translated hispoem, which is entitled “Forenoon Sleep”.Since only poets can translate poetry, Al-Sayyab’s translation for Prévert’spoem met the content not the form. It had no relation with the French text because Al-Sayyab substituted even the title with a new one that relates to the content. The translation was like the modern Arabic poetry and it had the poetic style peculiar to Al-Sayyab.It is true that translation is a rewriting for the original text, keeping its sense. Translation for Al-Sayyab, however, is more like a creation than mere transferring from the origin.This study concludes that Prévert and Al-Sayyab are two poles of modern poetry. The first participated in the emergence of Surrealism while the second was a pioneer of modern blank verse in Iraq and Arabic world. As both witnessed the wars and crisis of the twentieth century, they had a revolutionary thought rejecting injustice and looking for freedom and independence. If Prévert is known for his simplicity in writing, Al-Sayyab’s poetry is distinguished by rigorous language and long- feet poems.